Harvard Business School confidential : secrets of success / Emily Chan. - Chan, Emily (John Wiley & Sons (Asia) ; John Wiley & Sons, 2009)
Harvard Business School is the iconic business school. An admission ticket to HBS is a hot commodity and an HBS degree is highly respected in the business world. This book, written by an HBS grad and seasoned businesswoman, tells you why. It is a distillation of the most valuable and pragmatic but yet easiest to learn concepts taught at HBS. --Product Description.